Commentary on "A non-reward attractor theory of depression": A proposal to include the habenula connection. (December 2017) - Loonen, Anton J.M.; Ivanova, Svetlana A.
Abstract: The non-reward attractor theory of depression describes this mood disorder as originating from a neuronal dysfunction that arises from increased vulnerability of a cortical network that detects failure to receive an expected reward. From an evolutionary standpoint, the concept that the cerebral cortex determines susceptibility to mood disorders is open to criticism. Instead, using the regulation of reward-seeking, and aversive events-avoiding behaviours of the earliest vertebrates as a start point, the authors have developed a theory of depression in which subcortical regulatory systems that involve the lateral and medial habenula, respectively, play a critical role in regulating these behaviours, and susceptibility to depressive symptoms. As these anatomical structures are well conserved through the evolution of early vertebrates to humans, the authors propose that this subcortical system remains operative. Integrating the evidence that supports the non-attractor theory of depression with this model of a subcortical regulation of behaviour, could offer fresh clues as to how psychological and biological factors interact to cause depression, as well as other mood and anxiety disorders.